Casdatifan shows durable response linked to HIF-2α biology in kidney cancer - Toni K. Choueiri; Jamie Merchan; Amita Patnaik; Alexandra Drakaki; Brian I. Rini; Sun Young Rha; Jae Lyun Lee; Moshe C. Ornstein; Rohit Kumar; Clara Hwang; Yusra Shao; Se Hoon Park; et al. (Nature, 2026)
Abstract Clear cell renal cell carcinoma (ccRCC) is largely driven by the transcription factor hypoxia-inducible factor 2α (HIF-2α) 1 . Here we show that monotherapy with casdatifan—an orally bioavailable, potent and selective HIF-2α inhibitor 2 —produces meaningful, durable antitumour activity with manageable safety in individuals with refractory metastatic ccRCC. Dose-expansion data from the ARC-20 study ( NCT05536141 ) are presented, including for the 100 mg once daily (QD) cohort ( n = 32) and the total cohort ( n = 127). Treatment discontinuation from casdatifan-related adverse events was infrequent (3%), and class-effect toxicities included anaemia and hypoxia. The confirmed objective response rates (ORRs) were 35% (95% confidence intervals (CI) = 19–55%; 100 mg QD) and 31% (95% CI = 23–40%; total); median progression-free survival (PFS) was not estimable (95% CI = 5.7–not estimable; 100 mg QD) and 12.2 months (9.4–20.6; total). Greater maximal reductions in serum erythropoietin were associated with improved clinical outcomes, including a higher ORR ( P = 0.001), lower rates of progressive disease ( P = 0.003) and longer PFS ( P = 0.006). Erythropoietin expression was restricted to cancer cells and was significantly higher at the mRNA level in patients with clinical benefit. Concordantly, HIF-2α protein expression and HIF-2α expression signature were associated with prolonged PFS. Overall, our findings show that casdatifan achieves meaningful, durable responses with manageable safety. These data establish a link between on-target HIF-2α pathway modulation, tumour biology and clinical efficacy.